Motivation for participating in continuous professional development among selected general practitioners in Kuala Lumpur, Malaysia: An exploratory case study / Low Kien Yong - Low, Kien Yong (2021)
Continues Professional Development (CPD) activities are life-long learning engagements for general practitioners. It can enhance their medical competencies across cognition, psychomotor and affection domains, hence upholding safety and quality of healthcare services. Literature reported that motivation drives learning among general practitioners. However, limited studies explored the motivation from an educational lens. This study explored motivation(s) from the Andragogy and Self-Determination Theory perspectives in promoting active learning among general practitioners. This study also explored their perceptions of the amended law enforcement in Malaysia that mandates CPD participation. Three private general practitioners in Kuala Lumpur consented to participate in this study. In-depth interviews were conducted using a semi-structured interview guide. The participants were prompted to elaborate on their opinions and provide examples. Recorded interviews were transcribed verbatim. The data were analysed using thematic analysis to generate themes and codes. No new theme emerged after the third interviewee. Private general practitioners were motivated when given the freedom to choose their preferred learning style(s), coupled with a flexible learning schedule and self-identified learning needs. Motivated general practitioners looked for resonance by relating learnt knowledge with their daily practice. They enjoyed socialising and professional networking elements of these learning activities. Their learning was driven by internalised value and personal interest. They continuously improved their competency to solve real-life problems at their workplace by learning. They perceived the mandate as a positive reinforcement that acting as external motivation. However, iv measures on competence indicators after learning were desired. This study reported that understanding motivation from an Andragogy perspective could promote learning among general practitioners towards learning activities. Fulfilment of their autonomy, relatedness and competency need could enhance learning motivations. Recommendations are made for the CPD organisers on how to apply Andragogy and Self-Determination Theory in curriculum development. Keywords: Continuous Professional Development (CPD), Adult Learners, General Practitioners (GPs), Andragogy, Self-Determination Theory (SDT)